ENHANCEMENT OF NATURAL DYE FROM BUTTERFLY PEA (CLITORIA TERNATEA LINN.) BY MEMBRANE AND COPIGMENTATION TECHNOLOGY - Heriyanto, Vanessa
The butterfly pea flower (Clitoria ternatea Linn.) is a native flower of Ternate, Indonesia, rich in anthocyanins. Anthocyanins are a group of natural blue-purple phenolic pigments with high antioxidant activity and proven health benefits. However, the use of butterfly pea flower as a natural food colorant is still limited due to its stability issues. The flavylium cation structure of anthocyanins is highly susceptible to degradation, which is a significant drawback. In this study, the effects of copigmentation methods were explored as a means to enhance the stability of anthocyanins in natural colorants derived from the butterfly pea flower. The research was divided into three stages: extraction, sterilization, and copigmentation. The extraction with variations in ratios of 1:3, 1:5, 1:10, 1:15, 1:20, 1:23, and 1:30 over 10, 20, and 30 minutes. The extraction ratio and time parameters affected the extracted anthocyanin content, with the ratio of 1:15 and 30 minutes extraction yielding the highest anthocyanin content. Copigmentation involves the formation of more stable anthocyanin complexes that are resistant to light, oxygen, and temperature increases. The concentrated extract from the optimal extraction variation was then sterilized using ultrafiltration (UF) methods. Copigmentation was carried out with variations in the copigmentation method parameters, including the addition of copigment agents and self-association concentration. Variations of copigment agents included ferulic acid, gum arabic, and ascorbic acid in molar ratios of 1:25, 1:50, and 1:75, and concentration using osmotic membrane distillation (OMD) to reach 1,5, 2, and 2,5 times. Various copigmentation methods affect the first-order anthocyanin degradation reaction rate constant. The addition of gum arabic at a 1:50 molar ratio produced the most stable anthocyanin complex against light degradation for 12 days and oxidation for 7 days, with k values of 0,031 days-1 and 0,03 days-1 . The addition of ferulic acid at a 1:50 molar ratio was the most stable against thermal degradation for 3 hours, with k values for temperatures of 30°C, 50°C, and 70°C being 0,6x10-3 , 0,7x10-3 , and 1,3x10-3 minutes-1 . Copigmentation can reduce the resulting k values, making copigmentation a feasible method to pursue.